2009
DOI: 10.1021/bc800357j
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Arrays for the Selective and Efficient Capturing of Viral Particles

Abstract: We describe microarrays of receptors on gold/glass substrates for the selective capturing of viral particles at high density. Microscale gold squares were surface-modified with alkanethiol derivatives which enabled the immobilization of the His(6)-tagged virus-binding domain from the very-low density lipoprotein (VLDL) receptor. The free glass areas surrounding the gold squares were passivated with a dense film of poly(ethylene glycol) (PEG). As assessed by atomic force microscopy, human rhinovirus particles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Nanoscale protein patterns have a number of applications such as biosensing [1,2], control of cell adhesion and 5 Authors contributed equally to this work. 6 Address for correspondence: 1 Medical Center Drive, PO Box 9530 Morgantown, WV 26505, USA.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoscale protein patterns have a number of applications such as biosensing [1,2], control of cell adhesion and 5 Authors contributed equally to this work. 6 Address for correspondence: 1 Medical Center Drive, PO Box 9530 Morgantown, WV 26505, USA.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Moreover, several notable studies have shown that nanostructured quartz surfaces dramatically enhance the biosensor detection sensitivity. [6,7] In recent decades, plasma-related technologies have been employed for surface processing of various materials and for the production of nanostructured materials in both research and industrial settings. Surface processing using plasma-related technologies can be categorized into two types: 1) surface modification, which results in a change in the chemical composition of a surface; and 2) selective dry-etching using reactive ionic species produced by a plasma, which makes it possible to fabricate nanometer-scale patterns on high-end materials.…”
Section: Introductionmentioning
confidence: 99%
“…As representative model system, we chose films composed of PEG with a molecular weight of 500 D and 5000 D. These two differently sized polymers exhibit strikingly different conformational preferences: short chains are helical and parallel aligned while long PEG polymers are highly curved and looped (Scheme 1). 46 The polymer chains were covalently grafted via terminal trialkoxysilane groups 19,47,48 onto ITO-coated substrates (Scheme 1). The PEG 500 and PEG 5000 films were examined with three specific objectives: (i) to confirm that the polymeric films are dense and homogeneous, (ii) to probe the permeability of small molecules through the PEG films, and (iii) to demonstrate their ability to reject the nonspecific adsorption of large proteins and thereby provide evidence for their semipermeability.…”
Section: Introductionmentioning
confidence: 99%